Sosialisasi Keamanan Jajanan Makanan Terhadap Kesehatan Ibu-Ibu PKK Jorong Tanjung Barulak, Nagari Kubang Kabupaten 50 Kota - Helga Yermadona; Femi Earnestly; Firdaus; Muchlisinalahuddin; Sri Wahyuni (Universitas Lancang Kuning, 2022)
The presence of street food in Kubang village varies greatly in the form of light and heavy snacks. Since the mothers in Jorong Tanjung Barulak have activities to help their husbands in farming, they prioritize buying snacks for family daily food needs that focuses on being full and delicious, without paying attention to nutrition and its effects. Various diseases can appear such as diarrhea and poisoning. The mother lacking time and the awareness to make their own family meals is a problem. Giving information about the safety street food is necessary in order they can intelligently choose snacks, know the good foods and not good for their children, educate the types healthy and practical food to make by themselves that lacks synthetic dyes, preservatives, and flavor enhancers. The increase of the healthy food knowledge is known from the results of the questionnaires distributed before and after from 36% to 86.67%.